An unusual primary biphasic neuroendocrine carcinoma of lung associated with ectopic ACTH production and Cushing's syndrome - Hamid Kazerouni, A; Neil Walker, J; Grossman, AB; Chetty, R (2014)
A 62-year old female presented with signs and symptoms of Cushing's syndrome. The source of the ectopic ACTH was a left lung lower lobe neuroendocrine tumour composed of two cell types: epithelioid and spindle shaped cells and; a second component of smaller, uniform round neuroendocrine cells. The tumour did not conform to any of the recognized lung neuroendocrine categories and an atypical carcinoid was the best fit based on mitotic count (6 per 10 high power field). This case highlights unusual histology for a pulmonary neuroendocrine tumour and also the nomenclatural difficulties associated with the current classification. © 2014 Elsevier Ltd. All rights reserved.